Hibridisme i autoreferència en el fantàstic d’Espiral, de Manuel Baixauli - Gregori Soldevila, Carme (Studia Romanica Posnaniensia, 2018)
The aim of this paper is to define and to analyse the fantastic universe of short stories by Manuel Baixauli published in the volume Espiral (2010), an original and highly significant example of modern fantastic literature that has abolished the real and imaginary borders, that is to say a significant example of fantastic literature conceived as a language phenomenon. The conception of reality integrates and naturalises the supernatural and the irrational in a vision that joins multiple dimensions and perspectives of reality. The self-referential component is also of essential importance in this fantastic, which assimilates and exhibits themes and motifs of inherited traditions in a fully conscious way. Baixauli reflects on the ways of perception and representation of reality, in a proposal in which he combines elements that come from some forms of genre whithin the fantastic tradition. And he does it with full awareness of the linguistic and cultural condition of the referents he uses, exploring implicit meanings, metaphorical value, expectations they generate, etc. A literature that, from the point of view of fantastic literature, opts for hybridism and self-reference.